Cucumaria in Russian Waters of the Barents Sea: Biological Aspects and Aquaculture Potential - Dvoretsky, Alexander G.; Dvoretsky, Vladimir G. (Frontiers in Marine Science, 2021)
Sea cucumbers are a popular luxury and delicacy food items in Asian markets. These echinoderms possess a wide range of bioactive substances that can be used to produce pharmaceutical products. Recent depletion of natural populations of sea cucumbers requires involving new objects both in commercial harvesting and aquaculture. The northern sea cucumber Cucumaria frondosa is the most abundant sea cucumber in the Barents Sea. In this paper, we summarized literature data on the biology of this polar species to evaluate its fishery and aquaculture potential in the area. This eurythermic sea cucumber is typically occurs at 20–100 m depth. Cucumaria mainly colonize rocky or pebbly bottoms. Their main food items are detritus, pellets, phytoplankton, and small planktonic crustaceans. Spawning is registered in February–May. The age of commercial specimens (body length 25–30 cm, wet weight 300–350 g) is 10 years. The most abundant stocks of C. frondosa are registered in the central and south-eastern parts of the sea. Due to the low growth rate of Cucumaria the most appropriate cultivation method for these holothurians is a combination of larval culture and sea ranching. Coastal sites of the Barents Sea merit all the criteria for sea ranching of Cucumaria, but the development of their extensive aquaculture requires significant investments with long pay-back periods.